Roberto Juarroz y José Ángel Valente - Saldana, Alfredo (Ars et humanitas, 2017)
Questioning the capacity of language to stabilize and control reality, thus pointing to the precariousness of any word-based knowledge, has become a recurrent theme of contemporary poetry. The Argentinean Roberto Juarroz (1925-1995) and Spanish José Ángel Valente (1929-2000), who both maintained an intense and radical relationship with language, are the most representative authors of a reflexive, metapoetic form of writing, a poetry of great conceptual density that provides a permanent meditation on the word and its capacity to generate reality. Both men committed themselves to the project of stretching the limits of language, finding in the void not symbols of negativity, but opportunities to generate new meaning.
Keywords: argentinska književnost; Juarroz, Roberto; nič; pesniki; praznina; primerjalna književnost; sodobna poezija; španska književnost; tišina; Valente, José Ángel